Study on mechanical pretreatment process of palm oil mill effluent (POME) - Noor Hazira, Abu Bakar (2006)
Palm oil mill effluent (POME) has been identified as one of the major sources of aquatic pollution in Malaysia. Due to its high strength and economic importance with more than 330 palm oil mills in operation, Malaysia produces about 10.6 million tones of crude palm oil annually, accounting for 47% of the total world production, and concomitantly generates 27 x 10 6 m 3 POME. This highly polluting wastewater can therefore cause severe pollution of waterways due to oxygen depletion and other related effects. The presence of oil-waste makes the bio-degrading process of the effluents difficult as oil inherently difficult to disintegrate. The aim of the proposed process in this study is both the reduction of pollution caused by the wastes and the selective separations of several useful products that are present such as polyphenol. Pretreatment process was carried out by using high speed centrifuge which the suspended solids are removed. Through the pretreatment, it helps to reduce the viscosity up to 22.3% and the acidity of POME. In addition, it will clarify the POME by reducing its turbidity value up to 32.4% along with the improvement of POME quality by decreasing the BOD and COD values. The polyphenol compound, (+)-catechin in POME was tracked by HPLC and it can only be separated chemically or biologically.